Lactulose-Induced Ischemic Colitis: A Rare Presentation and an Overview of Possible Etiologies of the Disease - Umar, Zaryab; Ilyas, Usman; Shah, Deesha; Nso, Nso; Foster, Allison; Zirkiyeva, Milana (Curēus (Palo Alto, CA), 2022)
Ischemic colitis is one of the most common ischemic pathologies of the gastrointestinal system and can be divided into non-gangrenous and gangrenous forms. The pathophysiology involves restricted blood supply to the colonic mucosa. Several risk factors have been implicated in the development of ischemic colitis. Lactulose, one of the mainstay therapies for the treatment of hepatic encephalopathy in patients with cirrhosis, has been rarely reported as a cause of ischemic colitis. To the best of our knowledge, there has been only one case report associating lactulose use with the development of ischemic colitis. The exact pathophysiology is unknown but might be associated with the fermentation of lactulose by intestinal bacteria, causing gaseous distention and increasing the intraluminal pressure. We present the case of a 77-year-old African American male, a known case of non-alcoholic liver cirrhosis with portal hypertension and esophageal varices, brought in by his family to the emergency department for altered mental status, non-bilious vomiting, abdominal distension, and pain for one day. On physical examination, the patient had upper extremity asterixis and was alert but disoriented to place and person. Diagnostic paracentesis was performed, which revealed leukocytosis, predominantly neutrophils. The patient was admitted for spontaneous bacterial peritonitis and hepatic encephalopathy with decompensated liver cirrhosis. The patient was started lactulose with a goal of three to four bowel movements per day. Despite adequate treatment, the patient continued to develop worsening mental function and abdominal distension. This was later followed by a bloody bowel movement. Laboratory assessment showed an elevated white blood cell count, worsening kidney function, and high anion gap metabolic acidosis. CT scan revealed dilated loops of bowel with air and fluid along with submucosal wall edema, findings suggestive of ischemic colitis. Given the poor prognosis and the patient's condition, colonoscopy was deferred. Lactulose was discontinued, as it was thought to be a contributing cause of the patient's ischemic colitis. His condition continued to deteriorate, and he passed away on Day 18 of admission.